Applications of "three-threads-measuring-system" in the swimming flume - Yang, H. H.; Li, X. H.; Yu, W. D.; Xu, X. H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to describe the measurement principles of "three-threads-measuring-system" and its applications. 2 figures show exemplary time histories for 3D velocity during freestyle and breaststroke swimming. More detail parameters can be calculated by a self-developed software. Major parameters, including Max velocity, Min velocity, velocity variation, stroke frequency, distance per stroke, are averaged over 10 stroke cycles. Results indicate: 1) freestyle and breaststroke show different cycle characteristics in the 3D velocity curves; 2) velocity fluctuation(y direction) can be used to determine swimmer`s technique characteristics in freestyle.